Reality is not Literature’s Alibi - Touche Gafla, Ofir (MiKAN, 2021)
This essay describes the relationship between reality and fiction in Adaf s novels and demonstrates six degrees of fiction in his works in an attempt to unearth some of the secrets of his writing.